Crop wild relatives inventory and conservation in the Primorsky Region of the Russian Federation - G. V. Talovina; E. V. Aistova (Труды по прикладной ботанике, генетике и селекции)
Background. The Primorsky Region is the most floristically diverse region of the Russian Federation and the Russian Far East because of the richness of the local endemic vegetation. Representatives of many species can be used as medicinal, food, forage and ornamental plants. In order to conserve plant genetic resources (PGR) of the Primorsky Region, specific composition of crop wild relatives (CWR) was inventoried. A complete CWR inventory is the fundamental basis for the development of in situ conservation as an integral part of a system of science-based rational use of the genetic diversity. A taxonomic analysis of the list has revealed the native/adventive species ratio. The species were ranked according to their economic value and the criterion of rarity and vulnerability. CWR representation in the reserves of the Primorsky Region was studied and recommendations concerning priority CWR species identification and in situ conservation issued.Materials and methods. The study was based both on literature data and on the authors' collecting mission materials obtained by means of the route exploration method. CWR taxonomic analysis employed the common floristic method. Aspects of CWR conservation in the Primorsky Region were developed using a unified methodology for CWR in situ conservation in Russia.Results and conclusions. The analysis has resulted in the identification of 442 vascular plants species from 120 genera and 37 families representing CWR in the Primorsky Region. CWR amount to about 16% of the entire flora of the region. Priority conservation has been recommended for 143 species. Most successfully CWR species can be conserved within the specially protected natural territories. CWR are represented in the following nature reserves of the Primorsky Region: Ussuriysky (151 species), Sikhote-Alinsky (143 spp.), Kedrovaya Pad (128 spp.), Lazovskoye (119 spp.), Dalnevostochny Morskoy (67 spp.) and Khanka (59 spp.). Adventive species amount to 42.5% among CWR of the Primorsky Region, that is, their fraction is smaller than the general figure for the regional flora. The smallest fraction of adventive species among CWR was detected in the Dalnevostochny Morskoy, Sikhote-Alinsky and Kedrovaya Pyad nature reserves (11.9%, 13.2% and 13.3%, respectively). The fraction of invasive species among CWR was found to be the largest (33.6%) in the Lazovsky Reserve. The average figures were recorded for the Khanka and Ussuriysky reserves (23.7% and 17.9%, respectively).